FRI0212 Associations of ERAP1, IL23R and PTGER4 Polymorphism with Radiographic Severity of Ankylosing Spondylitis. (9th June 2015) - Ozen, G.; Deniz, R.; Eren, F.; Erzik, C.; Aydin, S.Z.; Inanc, N.; Direskeneli, H.; Atagunduz, P.
Abstract : Background: Ankylosing spondylitis (AS) is an inflammatory disease predominantly affecting spine which may lead to syndesmophyte formation and disability. However, the new bone formation and the radiographic severity of AS shows great variance that some patients never develop syndesmophytes throughout the entire disease duration, whereas some develop spinal fusion. The genetic determinants of this variance has not been identified yet in a well-defined mild-radiograhic AS and severe-radiographic AS. Objectives: To determine the association between ERAP1, IL23R and PTGER4 polymorphisms and radiographic severity of AS and secondly to identify clinical characteristics associated with severe radiographic AS. Methods: rs27044 and rs30187 ( ERAP1 gene), rs11209032 ( IL23R gene) and rs10440635 ( PTGER4 gene) single nucleotide polymorphisms (SNP) were genotyped in total of 199 AS patients (F/M: 83/116, mean age: 42.1±11.0 years, 62.8% HLA-B27 [+]) fulfilling the 1984 modified New York criteria for AS. Patients were classifed as severe-radiographic AS and mild-radiographic AS according to modified Stoke AS spinal score (m-SASSS). Mild AS is defined as having m-SASSS of "0" despite ≥10 years of disease duration. Whereas severe AS is defined as having m-SASSS of >20 (without counting scores "1") regardless of the disease duration. Results: Fifty eight patients (F/M=9/49, mean age 50.7±9.3, disease duration 21.9±7.0 years) were classified as severe AS, 141 patients (F/M=74/67, mean age 38.3±9.1, disease duration 13.6±4.9 years) were classified as mild AS. Severe group had significantly higher m-SASSS scores (48.5±18.3 vs 0) ( P <0.001). The genotype frequency of the entire cohort is shown in Table 1 . There were no significant differences in the distributions of ERAP1 rs27044 and rs30187, IL23R rs11209032 and PTGER4 rs10440635 SNP genotypes between severe and mild AS (Table 2 ). The genotype frequencies did not change when severe and mild AS patients were categorized according to gender or HLA-B27 status. Concerning clinical and demographic characteristics, it was found that majority of severe AS patients were males (84.5%) and severe AS patients had significantly higher coxofemoral joint involvement (43.1% vs 22.2%, P =0.003), uveitis (25.9% vs 12.8%, P =0.024), anti-TNF usage (70.7% vs 39.7, P <0.001) and HLA-B27 positivity (75.9% vs 57.4%, P =0.026) compared to mild AS. In multi-variate analysis male gender (OR=0.19, 95% CI [0.087-0.42], P <0.0001) and coxofemoral joint involvement OR=2.13, 95% CI [1.06-4.25], P =0.033) were independently associated with severe AS. Conclusions: Our data with a well-defined categorization of mild and severe-radiographic AS underline that ERAP1 rs27044 and rs30187, IL23R rs11209032 and PTGER4 rs10440635 SNPs are not associated with radiographic severity of AS. Whereas male gender and coxofemoral joint involvement are associated with severe-radiographic AS. Disclosure of Interest: None declared